Wang-MacDonald d-Wave Vortex Cores Observed in Heavily Overdoped Bi_{2}Sr_{2}CaCu_{2}O_{8+δ} - Tim Gazdić (American Physical Society, 2021)
Low-magnetic-field scanning tunneling spectroscopy of individual Abrikosov vortices in heavily overdoped Bi_{2}Sr_{2}CaCu_{2}O_{8+δ} unveils a clear d-wave electronic structure of the vortex core, with a zero-bias conductance peak at the vortex center that splits with increasing distance from the core. We show that previously reported unconventional electronic structures, including the low-energy checkerboard charge order in the vortex halo and the absence of a zero-bias conductance peak at the vortex center, are direct consequences of short intervortex distance and consequent vortex-vortex interactions prevailing in earlier experiments.